The Suspension of the Advocate Oath and Its Implications for the Criminalization of the Legal Profession - Lutfiadi, Lutfiadi; Wardani, Win Yuli; Ismail, Mahsun ; Mohammad, Mohammad; Sari, Insana Meliya Dwi Citra Aprilia (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The suspension of advocates’ oaths by the High Court raises fundamental legal issues concerning the professional legitimacy of advocates and the public’s right to legal aid. This study examines the legal basis for such suspension within the framework of Law No. 18 of 2003 on Advocates, evaluates the status of advocates following suspension, analyzes potential criminal implications, and explores broader policy consequences for human rights, particularly access to justice. Employing a normative juridical method, the research draws upon approaches from legal dogmatics, legal theory, and legal philosophy, supported by analysis of statutory law, legal scholarship, and relevant judicial decisions. The findings reveal that the suspension of advocates’ oaths lacks explicit legal grounding, constitutes an ultra vires act, and contravenes the principle of legality. Advocates whose oaths are suspended remain professionally legitimate and cannot be subject to prosecution except through mechanisms established by professional organizations or a binding judicial ruling. In conclusion, the unilateral suspension of oaths generates legal uncertainty, undermines public access to legal aid, and underscores the necessity of ensuring legal certainty and safeguarding both advocates’ rights and the public’s right to justice.